Assessing the impact of applying individual discount rates in power system expansion of Ecuador using OSeMOSYS - Roberto Heredia Fonseca; Francesco Gardumi (International Journal of Sustainable Energy Planning and Management, 2022)
The development of the electricity supply sector needs data and energy system models to aid government instances to achieve optimal decision-making. Since 2006, Ecuador has faced gradual changes in the electricity sector and invested more than 11 billion dollars in expanding the generation. We use an open-source model generator in the present study and develop the first long-term generation expansion model for Ecuador. We select specific social and hurdle rates to represent the government's decision to mobilize private energy infrastructure investments. We build scenarios for social and hurdle rates to evaluate the sensitivity of renewable and conventional generation technologies to such rates. Results show that medium and large hydropower have a low sensitivity to discount rates. Medium and large hydropower plays a significant role in the energy mix in the mid and long-term, regardless of the discount rate. Results from this model find no significant contribution of non-hydro renewables. Among these, only geothermal reaches around 160 MW for all scenarios. Installing geothermal and hydropower minimizes generation from conventional technologies until 2034; then, CCGT installations increase CO2 emissions above 2020 levels.